The renewable energy landscape in Benin: an analysis and review of barriers, targets, policies and actions for a clean energy transition - CHETANGNY, Patrice Koffi; YOTTO, Habib Conrad Sotiman; Aredjodoun, Jacques G.; HOUNDEDAKO, SOSSOU; CHAMAGNE, Didier; BARBIER, Gérald; VIANOU, Antoine (My University, 2021)
Sustainable development goals stipulated at its seventh point “Ensure access to affordable, reliable, sustainable and modern energy for all”. To achieve this goal, renewable energy plays important role to enable all nation get access to electricity. The case of Benin is crucial because only 9% of people leaving in rural area have electricity and only 15 % of its total electricity consumption came from renewable energies, against 85 % of production from fossil fuels. Many actions are taken to increase the percentage of renewable energy and ensure energy autonomy of the country. Also, the purpose of Benin is to achieve a Renewable Energy Target of 20 percent by 2030. In this article, we summarize various sources and potential of renewable energy available in Benin. We then analyze the problems undermining the policy of developing renewable energy and propose the best mechanisms and actions for achieving these targets. This document describes key policy frameworks, of investments and incentives actions.
Keywords: Renewable energy sources; Mechatronics; Greenhouse effect; Sociology; Government; Production; Reliability